Test the Difference in Service Quality and Online Promotion for the Shopee and Tiktok Shop Applications - Jesika Tamaria; Syti Sarah Maesaroh; Adam Hermawan (CV. ULIL ALBAB CORP, 2024)
This research examines the differences in service quality and effectiveness of online promotions between the Shopee and Tiktok Shop applications in the Indonesian e-commerce market. With increasing competition in the e-commerce sector, understanding the differences in service quality and promotional strategies of each platform becomes crucial. This research method uses comparative quantitative involving generation Z in the DKI Jakarta area as active users of both applications to evaluate various aspects of service quality, such as responsiveness, ease of use, and customer support, as well as the effectiveness of online promotions, including offers, discounts, and advertising. The sampling technique uses probability sampling with a random sampling approach. Data was collected through a questionnaire and analyzed using an independent sample test to compare the differences between Shopee and Tiktok Shop. Research findings show that these two applications have differences in sig values. (2-tailed) < 0.05 and Shopee is superior to Tiktok Shop with the average value of Shopee's service quality and online promotions being 45.7400 and 44.2200, while Tiktok Shop is 44.2200 and 42.5100. With these findings, it is hoped that they can provide insight into the strengths and weaknesses in the service and promotion aspects of each application, as well as provide strategic recommendations for improving services and promotions in the future, both for application managers and consumers.